x^3 + 2x^2 + 3x + 6 = 0
делаем преобразование:
x^3 + 2x^2 + 3x + 6 = (x+2)*(x^2+3)
решаем:
x+2=0
приводим подобные:
x+2=0
решаем:
x^2+3=0
приводим подобные:
x^2+3=0
:
x^2=-3
ответ: x=-2
x^4+x^3-8x-8=0
делаем преобразование:
x^4+x^3-8x-8=(x-2)*(x+1)*(x^2+2x+4)
решаем уравнение:
x-2=0
приводим подобные:
x-2=0
:
x=2
решаем уравнение:
x+1=0
приводим подобные:
x+1=0
:
x=-1
решаем уравнение:
x^2+2x+4=0
приводим подобные:
x^2+2x+4=0
дискриминант:
d=b^2-4ac
d=2^2-4*1*4=-12
действительных корней нет:
d< 0
ответ: x=-1, x=2
Поделитесь своими знаниями, ответьте на вопрос:
Решите систему уравнений: плез
sin^2 3x+3 cos^2 3x-4 sin (п/2+3х) cos(п/2+3х)=0
sin^2 3x+3(1- sin^2 3x) -2 *2sin2(п/2+3х)=0
sin^2 3x+3-3sin^2 3x - 4cos2x = 0
-2sin^2 3x - 4( cos^2 x-sin^2 x)= 0
-2sin^2 3x -4cos^2 x + 4sin^2x=0
2sin^2 x -4(1-sin^2x)=0
2sin^2 x - 4 +4sin^2 x=0
6 sin^2 x=4
sin^2x=4/6
sin^2 x=2/3
sinx=2/3 sinx=-2/3
x=(-1)^n arcsin(2/3)+пn x=(-1)^n arcsin(-2/3)+пn
x=(-1)^n -arcsin(2/3)+пn
x=(-1)^n+1 arcsin(2/3)+пn